2023
DOI: 10.1055/a-2116-9930
|View full text |Cite
|
Sign up to set email alerts
|

Use of endoscopic submucosal dissection or full-thickness resection device to treat residual colorectal neoplasia after endoscopic resection: a multicenter historical cohort study

Clara Yzet,
Yann Le Baleur,
Jérémie Albouys
et al.

Abstract: Introduction Residual colorectal neoplasia (RCN) after previous endoscopic mucosal resection is a frequent challenge. Different management techniques are feasible including endoscopic full-thickness resection using the full-thickness resection device (FTRD) system and endoscopic submucosal dissection (ESD). We aimed to compare the efficacy and safety of these two techniques for the treatment of such lesions. Methods All consecutive patients with RCN treated either using the FTRD or by ESD were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Another benefit of the FTRD procedure seems to be the lower training requirement compared to ESD to obtain satisfactory R0 rates with efficient procedure time. However, because the resection mechanism involves pulling the lesion into the cap, lesion size becomes a limiting factor, inevitably leading to a decrease in R0 resection rates as the size of the lesion increases, with R0 rates falling to 33% for lesions larger than 3 cm [38].…”
Section: Benefits and Limitationsmentioning
confidence: 99%
“…Another benefit of the FTRD procedure seems to be the lower training requirement compared to ESD to obtain satisfactory R0 rates with efficient procedure time. However, because the resection mechanism involves pulling the lesion into the cap, lesion size becomes a limiting factor, inevitably leading to a decrease in R0 resection rates as the size of the lesion increases, with R0 rates falling to 33% for lesions larger than 3 cm [38].…”
Section: Benefits and Limitationsmentioning
confidence: 99%
“…A recent French multicenter retrospective study reported data extracted from the prospectively collected national databases of ESD cases and the FTRD register, including a total of 275 patients [19]. The en bloc and R0 rates were significantly higher for ESD on multivariate analysis after adjustment for lesion size; AEs were also higher in the ESD group.…”
Section: Adverse Events N (%)mentioning
confidence: 99%